Early modern herbals and the book trade : English stationers and the commodification of botany - Neville, Sarah (Assistant professor of English) (Cambridge University Press, 2022)
Between 1525 and 1640, a remarkable phenomenon occurred in the world of print: England saw the production of more than two dozen editions identified by their imprints or by contemporaries as 'herbals'. Sarah Neville explains how this genre grew from a series of tiny anonymous octavos to authoritative folio tomes with thousands of woodcuts, and how these curious works quickly became valuable commodities within a competitive print marketplace. Designed to serve readers across the social spectrum, these rich material artifacts represented both a profitable investment for publishers and an opportunity for authors to establish their credibility as botanists. Highlighting the shifting contingencies and regulations surrounding herbals and English printing during the sixteenth and early seventeenth century, the book argues that the construction of scientific authority in Renaissance England was inextricably tied up with the circumstances governing print. This title is also available as Open Access on Cambridge Core at doi.org/10.1017/9781009031615.
Title from publisher's bibliographic system (viewed on 24 Dec 2021).
Keywords: Herbals -- England -- History and criticism.; Publishers and publishing -- England -- History.; Botany -- England -- History.